Thermal Scanning of Dental Pulp Chamber by Thermocouple System and Infrared Camera during Photo Curing of Resin Composites - Hamze, Faeze; Ganjalikhan Nasab, Seyed Abdolreza; Eskandarizade, Ali; Shahravan, Arash; Akhavan Fard, Fatemeh; Sinaee, Neda (Iranian Endodontic Journal, 2018)
Introduction: Due to thermal hazard in composite restorations, this study was designed to scan the pulp temperature by thermocouple and infrared camera during photo polymerizing different composites. Methods and Materials: A mesio-occlso-distal (MOD) cavity was prepared in an extracted tooth and the K-type thermocouple was fixed in its pulp chamber. Subsequently, 1 mm increment of each composites were inserted (four composite types were incorporated) and photo polymerized employing either LED or QTH systems for 60 sec while the temperature was recorded with 10 sec intervals. Ultimately, the same tooth was hemisected bucco-lingually and the amalgam was removed. The same composite curing procedure was repeated while the thermogram was recorded using an infrared camera. Thereafter, the data was analyzed by repeated measured ANOVA followed by Tukey’s HSD Post Hoc test for multiple comparisons (α=0.05). Results: The pulp temperature was significantly increased (repeated measures) during photo polymerization (P=0.000) while there was no significant difference among the results recorded by thermocouple comparing to infrared camera (P>0.05). Moreover, different composite materials and LCUs lead to similar outcomes (P>0.05). Conclusion: Although various composites have significant different chemical compositions, they lead to similar pulp thermal changes. Moreover, both the infrared camera and the thermocouple would record parallel results of dental pulp temperature. Keywords:Exothermic Reaction; Infrared Camera; Light Curing Unit; Pulp Temperature; Resin Composite; Thermocouple